2019
DOI: 10.1002/we.2339
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of offshore extreme wind from wind‐wave coupled modeling

Abstract: A coupledwind‐wave modeling system is used to simulate 23 years of storms and estimate offshore extreme wind statistics. In this system, the atmospheric Weather Research and Forecasting (WRF) model and Spectral Wave model for Near shore (SWAN) are coupled, through a wave boundary layer model (WBLM) that is implemented in SWAN. The WBLM calculates momentum and turbulence kinetic energy budgets, using them to transfer wave‐induced stress to the atmospheric modeling. While such coupling has a trivial impact on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 49 publications
2
24
1
Order By: Relevance
“…However, the wave influences cannot be captured by a stand-alone atmospheric model through tuning model parameterizations [14]. Twenty-three years storms are simulated using an atmosphere-wave-coupled model, Larsen et al [15] found that the coupled model improves the wind simulation considerably when compared with the measurements from five offshore sites around Denmark, in particular when the mean wind speed at 10 m U 10 > 20 m s −1 . On the low wind and swell conditions, the wind simulation is improved when sea-state-dependent wind stress parameterization is implemented into an atmosphere-wave-coupled system [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, the wave influences cannot be captured by a stand-alone atmospheric model through tuning model parameterizations [14]. Twenty-three years storms are simulated using an atmosphere-wave-coupled model, Larsen et al [15] found that the coupled model improves the wind simulation considerably when compared with the measurements from five offshore sites around Denmark, in particular when the mean wind speed at 10 m U 10 > 20 m s −1 . On the low wind and swell conditions, the wind simulation is improved when sea-state-dependent wind stress parameterization is implemented into an atmosphere-wave-coupled system [12].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 2011, Wu et al 2015. Larsén et al (2019) used a wind-wave coupled system to draw up an extreme-wind atlas for the waters around Denmark. In general, there is still the challenge of too few measurements being available offshore, making it difficult to validate and improve modelling approaches.…”
Section: Development Of Methodologies and Applicationsmentioning
confidence: 99%
“…(2017a) and Larsén et al . (2019), which showed good performance when simulating storms events. Sea surface temperature is not updated during the simulation.…”
Section: Model Set‐upmentioning
confidence: 99%
“…In studies such as that of Larsén et al . (2019), which focuses on the estimation of extreme offshore wind speeds, correctly simulating both the intensity and the location of hundreds of storms is crucial for reliable statistics. Therefore, careful design of the LAM settings is required.…”
Section: Introductionmentioning
confidence: 99%